KAJIAN BENTUK, FUNGSI DAN MAKNA RAGAM HIAS RUMAH BOLON SIMALUNGUN BERDASARKAN TATANAN SOSIAL BUDAYA MASYARAKAT SIMALUNGUN - Roseilda Regita (ARTic, 2018)
This research, entitled "Study of Form, Function and Meaning of Decorations in Rumah Bolon Simalungun â€œTraditional Houseâ€ based on the culture society". This research, entitled "Study of Form, Function and Meaning of Decorations in Rumah Bolon Simalungun â€œTraditional Houseâ€ based on the culture society". In general this research is aimed to know the values of traditional buildings by using conceptions and cultural values of Simalungun specifically. Such as, to reveal the meaning inside of "Rumah Bolon Simalungun", describe everysingle part of the house. Including of, roof, wall, floor, and identify decorative pattern on the building. This research uses qualitative descriptive technique. Data was collected by documentation, observation, and interviews. Data analysis was conducted on the types of the building in terms from the principle of form, fuction, and meaning of ornamentation on the building Rumah Bolon Simalungun in Pematang Purba. This study was conducted to explore the traditional culture for Simalungun contained in traditional buildings that have been forgotten. Not all of the parts of traditional houses which can be understood as a description of the customary meaning of behavioral traits Simalungun society. In this building preservation efforts have repercussions far backwards that will come, that is for everyone, whether Simalungun people, the older generation or the younger generation as a successor or the heir of their culture that will understand and know well about the result of their native culture.